Factors affecting the ERP implementation in Indian retail sector: A structural equation modelling approach. Issue 7 (5th October 2015) - Garg, Poonam; Chauhan, Ajay
Abstract : Purpose: – The purpose of this paper is to make an effort in identifying and exploring the factors which may affect the success of ERP implementation in Indian retail sector. This paper also analyses the between the factors and their impact on the successful implementation of ERP using the structured equation modeling (SEM) approach. "Organizational, " "Technological, " "People" and "Project Management" are the examined factors. Design/methodology/approach: – A theoretical model is created that explains the factors which may affect the success of ERP implementation. Hypotheses were also developed to evaluate the interrelationship between affecting factors and success of ERP implementation. Empirical data is collected through survey questionnaire from practitioner like project sponsors, project managers, implementation consultants and team members who are involved in ERP implementation in retail sector to test the theoretical model. Findings: – Using SEM, it is found that 62.7 percent of the variations of ERP implementation success can be explained with the help of the model suggested in the research study. The finding also confirms that there is significant positive interrelationship between "Organizational, " "Technological, " "People, " "Project Management" and success of ERP implementation in Indian retail sector. Research limitations/implications: – The research is subject to the normal limitations of survey research. The study is using perceptual data provided by project sponsors, project managers, implementation consultants and team members who are involved in ERP implementation in retail sector, which may not provide clear measures of performance. However, this can be overcome using multiple methods to collect data in future studies. Practical implications: – Findings from this paper can provide greater understanding in the area of ERP implementation. This study will provide valuable insights to researchers, practicing managers and those who are planning to implement ERP in retail sector. Originality/value: – The study integrates the affecting factor with success of ERP implementation, i.e. "Organizational, " "Technological, " "People" and "Project Management" are the key drivers for the effectiveness and success of ERP implementation in Indian retail sector. Very few studies have been performed to investigate and understand this issue. Therefore, the research can make a useful contribution.